2017
DOI: 10.1080/09638288.2017.1294209
|View full text |Cite
|
Sign up to set email alerts
|

Provider-identified barriers and facilitators to implementing a supported employment program in spinal cord injury

Abstract: Implementation strategies need to be adjusted as implementation progresses and matures. The strategies that succeeded in this setting, which were situated in a real-world context of providing IPS as a part of SCI medical care, may inform implementation of IPS for other populations with physical disabilities. Implications for Rehabilitation Key facilitators to IPS in SCI implementation are integrating vocational staff with expertise in IPS and SCI on clinical rehabilitation teams and providing leadership suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Our study confirms that the barriers to VR and WP vary in time during inpatient rehabilitation. 24,29 Initially medical barriers such as fatigue, complications, and uncertainty about prognosis are the main experienced barriers; but by the time of discharge, medical complications, lack of importance, disability considerations such as accessibility, and knowledge of appropriate jobs as well as resources become more important barriers. Being aware of the dynamics in those barriers can guide us in optimizing VR.…”
Section: Discussionmentioning
confidence: 99%
“…Our study confirms that the barriers to VR and WP vary in time during inpatient rehabilitation. 24,29 Initially medical barriers such as fatigue, complications, and uncertainty about prognosis are the main experienced barriers; but by the time of discharge, medical complications, lack of importance, disability considerations such as accessibility, and knowledge of appropriate jobs as well as resources become more important barriers. Being aware of the dynamics in those barriers can guide us in optimizing VR.…”
Section: Discussionmentioning
confidence: 99%
“…2 Frontline clinicians and healthcare managers can provide essential macro-level perspectives on patient health service needs. [3][4][5][6][7] This key stakeholder input allows for successes to be documented and shared, but is also important for identifying gaps in care. A methodology that identifies facilitators and barriers to service provision is important for informing recommendations on future implementation efforts that address healthcare concerns.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…A methodology that identifies facilitators and barriers to service provision is important for informing recommendations on future implementation efforts that address healthcare concerns. 3,8 Here, we report the results of a survey of Veterans Health Administration (VHA) Compensated Work Therapy (CWT) program supervisors and frontline vocational rehabilitation specialists (VRSs) about their experiences with and perceptions of providing the evidence-based Individual Placement and Support (IPS) model of Supported Employment 9 (hereafter referred to as SE) to Veterans with TBI.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Cotner and colleagues (2017) found that barriers for veterans with SCI could be broken down into six categories. This included veteran-specific (personal characteristics, lack of transportation, fear of losing benefits), high caseload of employment specialists, lack of integrating the employment specialist into the SCI clinical team, employment specialist hiring and turnover issues, SCI clinical team unfamiliar with vocational rehabilitation, and difficulty obtaining resources (Cotner, Ottomanelli, O'Connor, & Trainor, 2017). However, having a good clinical team and employment specialists that specializes in SCI were major facilitators in employing individuals with SCI.…”
Section: Introductionmentioning
confidence: 99%